Impact of Superior Canal Dehiscence Syndrome on Health Utility Values: A Prospective Case-Control Study - Ocak, Ibrahim; Topsakal, Vedat; Van de Heyning, Paul; Van Haesendonck, Gilles; Jorissen, Cathérine; van de Berg, Raymond; Vanderveken, Olivier M.; Van Rompaey, Vincent (Frontiers in Neurology, 2020)
Introduction: Superior canal dehiscence syndrome (SCDS) is a condition characterized by a defect in the bone overlying the superior semicircular canal, creating a third mobile window into the inner ear. Patients can experience disabling symptoms and opt for surgical management. Limited data are available on the impact of SCDS on health-related quality of life (HRQoL) and disease-specific HRQoL more specifically. Objective: To perform a prospective analysis on generic HRQoL in SCDS patients compared to healthy age-matched controls. Methods: A prospective study was performed on patients diagnosed with SCDS and who did not undergo reconstructive surgery yet. Patients were recruited between November 2017 and January 2020 and asked to complete the Health Utility Index (HUI) Mark 2 (HUI2) / Mark 3 (HUI3) questionnaire. For the control group, age-matched participants without otovestibular pathology or other chronic pathology were recruited. The multi-attribute utility function (MAUF) score was calculated for the HUI2 and HUI3. Results of both groups were compared using the Mann-Whitney U test. Results: A total of 20 patients completed the questionnaire. Age ranged from 37 to 79 years with a mean age of 56 years (45% males and 55% females). The control group consisted of 20 participants with a mean age of 56.4 years and ranged from 37 to 82 years (35% males and 65% females). For the case group, median HUI2 MAUF score was 0.75 and median HUI3 MAUF score was 0.65. For the control group, the median scores were 0.88 and 0.86 respectively. There was a statistically significant difference for both HUI2 (p=0.024) and HUI3 (p=0.011). SCDS patients had a worse generic HRQoL than age-matched healthy controls. One patient with unilateral SCDS had a negative HUI3 MAUF score (-0,07), indicating a health-state worse than death. Conclusion: SCDS patients have significantly lower health utility values than an age-matched control group. This confirms the negative impact of SCDS on generic HRQoL, even when using an instrument that is not designed to be disease-specific but to assess health state in general. These data can be useful to compare impact on HRQoL among diseases.